Analisis Markov Chain, Quene Problem dan Decision Support System pada PT.UVW dan PT.XYZ - Nico Nainggolan; Wahyudin Wahyudin; Billy Nugraha (Industrial Engineering, Faculty of Engineering, Universitas Sebelas Maret, 2021)
Every customer wish to go to a workshop always consider in selecting the official workshop or the public. The high level of the intensity of the queue and the service provided make the customer consider in determining service for the owned vehicle. The purpose of this study is to determine the market share of the authorised and general. In addition the right strategy to attract customers so it remains to choose the workshop. Then the method that will be used gradually, starting from the markov chain, quene problem and the decision support system. To quene problem using the model multiple channel query system and decision support sytem using simple additipe weighting method. The results obtained gradually, starting from the market share for a period of 1 to 3 by 60% and 40% as a result of markov chain. While the results of the quene problem obtained the average arrival rate of 4 customers with a level of service of 1.02/h and waiting time for 30 minutes. As for the decision support system with a total labor cost to 5 mechanical man Rp.20.800/h and obtained the cost of waiting for customer Rp.79,000/day